ChemInform Abstract: Selective Access to Trisubstituted Macrocyclic E‐ and Z‐Alkenes from the Ring‐Closing Metathesis of Vinylsiloxanes. Issue 30 (4th July 2013) - Wang, Yikai; Jimenez, Miguel; Sheehan, Patrick; Zhong, Cheng; Hung, Alvin W.; Tam, Chun Pong; Young, Damian W.
Abstract Retention or inversion of alkene geometry during bromination depend on both ring size and steric relations in the substrate.